Reprodução em cativeiro do jurupecê Sorubim lima (Siluriformes, Pimelodidae) por meio de indução hormonal - Shibatta, Oscar Akio; Novelli, Jose Luiz; Pinheiro Dias, Joao Henrique; de Castro Britto, Sandro Geraldo [UNESP]; Caetano Filho, Mauro (Universidade Estadual de Londrina (UEL), 2011)
Sorubim lima is a migratory catfish that do not reproduce in lenthic environments such as those formed after construction of hydroelectric power plants. An alternative for conservation of the species in these environments is the stocking with fingerlings produced in captivity. The technique used to reproduce it in captivity was the induction by carp pituitary hormone, with dosage of 5 mg.kg(-1) for females (1 mg.kg(-1) in the first dose and 4 mg.kg(-1) in the second) and 3 mg.kg(-1) for males (1 mg.kg(-1) in the first dose and 2 mg.kg(-1) in the second), with an interval of 14 hours. The determination of extrusion moment of oocytes was made by monitoring the migration of nucleus from central to peripheral position. After UTA 264.5 (accumulated thermal units) the oocytes were obtained by compression of the ventral region of the female, and male were sacrificed for extraction of sperm. The eggs were kept in an incubator and the time of hatching of larvae was 370 UTA. The larvae were initially fed with plankton and showed no cannibalism. Moreover, they were not demanding about the food, accepting prepared rations after fifteenth day of life. The weight gain of larvae was very low even close to 20 mm in length (14 days), not exceeding 0.05 mg per day. After that both weight and length increased rapidly.
Reproduction of duckbill catfish Sorubim lima in captivity (Siluriformes, Pimelodidae) by means of hormonal induction
Keywords: Hipofization; migratory fishes; jurupece; catfish